2022
DOI: 10.3389/fnut.2022.858593
|View full text |Cite
|
Sign up to set email alerts
|

Age, an Important Sociodemographic Determinant of Factors Influencing Consumers' Food Choices and Purchasing Habits: An English University Setting

Abstract: The purchasing behaviors of university staff (n = 188) and their use of nutrition labels in making food choices were investigated by an online survey. The age of the participants significantly impacted their purchasing behaviors. This effect was not observed with other sociodemographic characteristics studied (level of education, gender, employment status and ethnicity). The impact of age on the extrinsic factors affecting food choice (personal preference, previous knowledge, convenience, religion/beliefs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Consumer choices can be influenced by various factors such as socio-demographics, traditions, health benefits, and taste, as well as drivers of consumption trends [ 25 , 27 , 32 , [51] , [52] , [53] , [54] , [55] ]. Consistent with these studies, our findings revealed that consumers' age had influence their preferences for the type of THIs beverages.…”
Section: Discussionmentioning
confidence: 99%
“…Consumer choices can be influenced by various factors such as socio-demographics, traditions, health benefits, and taste, as well as drivers of consumption trends [ 25 , 27 , 32 , [51] , [52] , [53] , [54] , [55] ]. Consistent with these studies, our findings revealed that consumers' age had influence their preferences for the type of THIs beverages.…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated that older adults have greater health risk perceptions (how individuals subjectively estimate and feel about the risks they face) compared with their younger counterparts (35,36) . Others have suggested that older age is associated with an increased tendency to use nutrition labels because of an increased interest in healthy eating as individuals get older (37) and/or increased efforts to meet specific dietary requirements as the metabolism declines with age (38) . However, the measure in our study was about whether the beverage with the sweetener disclaimer was healthy for children, not for themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors are involved in consumer food choice such as the health status of the consumer, religious beliefs like halal foods, philosophical beliefs like veganism, peer pressure, advertisements, quality of foods, ingredients, availability, and so on (Kershaw et al., 2019; Ogundijo et al., 2022; Puddephatt et al., 2020). Various techniques like sensory analysis and along with questionnaires are done to identify consumer behavior toward a product.…”
Section: Introductionmentioning
confidence: 99%